KONTRIBUSI PRODUK UPCYCLE PADA INTENTERIOR RUANG KOMERSIAL (STUDI KASUS KARYA ANDRE SURYAMAN PADA CAFÉ N RESTO THE BEAN GARDEN COFFE YOGYAKARTA): CONTRIBUTION OF UPCYCLED PRODUCTS TO THE INTENTERIOR COMMERCIAL SPACE (CASE STUDY OF ANDRE SURYAMAN'S WORK AT CAFÉ N RESTO THE BEAN GARDEN COFFEE YOGYAKARTA) - Achmad Lutfi; Ahadiat Joedawinata; Cama Juli Rianingrum (Universitas Trisakti, 2024)
Public space is an area or place where a community or community can gather to achieve the same goals and share stories about personal and group problems. One type of public space needed by the community is External Public Space, public facilities controlled by the private sector engaged in the commercial sector. In general, commercial space is a building or space that accommodates various business activities in it. In this study, we will discuss more about the role of upcycled products in the aesthetic elements of commercial space interiors. where currently café n restaurant no longer only offers food and beverage menus as a promotional strategy but also looks at several influencing factors to be able to increase the number of visitors, including cultural trends, social media, unique interior elements, comfortable and safe space concepts. The general objective of this research is to examine the role of upcycle products in the interior of commercial spaces, whether the presence of upcycle products can play a strong role in increasing the number of visitors. The specific goal is for upcycle products to become one of the supporting elements in the commercial space